A Multidimensional Comparison Assessing the Viability of Electric Vehicles in Jordan Across Key Performance Metrics - Mohammad Ahmad Ben Tarief; Salah Aldeen Qasim; Hisham Al-mujafet; Saif addeen Rababa; Suleiman Abu-Ein; Sakher Alaqbawe (Universitas Muhammadiyah Magelang, 2025)
This study presents the first field-based, OBD-II”“supported comparison of an electric vehicle (Changan Eado EV300) and a gasoline vehicle (Kia K3, 2019) under realistic Jordanian driving conditions. Using a 100 km mixed-route test and annualized projections, we evaluate energy consumption, operating cost, greenhouse-gas emissions (including battery manufacturing amortization), dynamic performance, cabin noise/comfort, and payback of purchase-price premium. Results indicate that, under predominant home charging, EV energy costs are reduced by over 60% relative to the tested gasoline vehicle, and operational COâ‚‚ emissions fall substantially when charged from a low-carbon grid; battery manufacturing increases lifecycle emissions but does not offset operational benefits under renewable charging scenarios. EVs deliver superior low-speed torque and smoother acceleration, while ICE vehicles retain advantages in raw range and refueling time. Payback of the purchase premium is estimated at 5.6”“7.5 years (without battery replacement) and can extend beyond a decade if mid-life battery replacement is required. Findings inform policy on charging infrastructure, tariff design, and battery-lifecycle management for Jordan and similar contexts.